Penggunaan Kartu Huruf dalam Meningkatkan Kemampuan Menulis Ejaan yang Benar Kelas 2 Madrasah Ibtidaiyah - Mutmainnah, Siti (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The development of reading as one of the basic abilities that a protÃ©gÃ© must possess, consists of several stages according to his age and developmental characteristics. This research is based on the low ability of the letters of ibitidaiyah madrassa students. In general, this research aims to improve the ability to recognize children with aspect 1) know and understand the letter 2) know and understand the sound of letters 3) write letters correctly. The specific purpose of this research is to improve the correct spelling through the use of letter cards for 2nd graders MI Ma'arif NU 2 Pancasan as many as 29 students. The step used in this study is by means of playing letter cards. The subject is ibtidaiyah madrassa students. A research procedure is research conducted through cycles of action as Classroom Action Research (CAR). Each step starts from: (1) planning, (2) the implementation of actions, (3) observations, (4) analysis and reflection results. The results prove that the use of letter cards can improve the ability to write the correct spelling for students of madrasah ibtidaiyah. Proven students' learning performance in the average initial condition when compared to the final condition of the child rose by 0.9 or 16.07%. From the results of this study is expected to be used as a consideration material for madrasah ibtidaiyah teachers in teaching the spelling of Bahasa Indonesia, especially in low classes in order to use letter cards as a learning aid.